AB1032 Profiles of Patients Aged over 80 Years with Rheumatoid Arthritis in Aora Registry. (15th July 2016) - Kobayashi, M.; Miyamoto, S.; Kashiwagura, T.; Sugimura, Y.; Konishi, N.; Urayama, M.; Ito, H.; Sakuraba, T.; Aizawa, T.; Abe, H.; Kamo, K.; Aonuma, H.; et al.
Abstract : Background: The proportion of the aging population is increasing worldwide. Currently, the population of aging individuals is the highest in Japan; the percentage of 65-year-old people is 26.7%, indicating an aged society. Furthermore, the proportion of elderly people over 65 years of age is the highest (33.6%) in Akita prefecture, Japan. Objectives: We investigated the data of patients with rheumatoid arthritis (RA) in various medical centers where in the orthopedic surgeons belonged to Akita Orthopedic Group on RA (AORA) in Akita. We think that Akita registry is the future vision for RA treatment. Methods: In this cohort study, we examined 324 of 2021 cases of patients aged ≥80 years (16.0%) from AORA registry in 2015 (average age, 66 years). Results: The average age of our cohort was 84 years (range, 80–99 years); of the 324 patients, 59 were men and 265 were women, and the average disease period was 14 years (range, 2 months–66 years). Two-hundred sixty eight (83.0%) cases were of elderly-onset RA (EORA). According to the Steinbrocker classification criteria, 82 cases were stage I; 69, stage II; 80 stage III; and 87, stage IV. Further, 77cases were cass 1; 128 class 2; 89 class 3; and 22, class 4. The past medical history of the patients was as follows: 176 cases of hypertension, 59 cases of respiratory diseases, 56 cases of heart diseases, and 38 cases of diabetes. MTX (average, 5.5 mg per week; range, 1–14 mg per week) was administered to 101 patients. Prednisolone (average, 3.8 mg/d; range, 1–12.5 mg/d) was administered to 170 patients. A combination of conventional systemic disease-modifying antirheumatic drugs was administered as follows: bucillamine to 97, salazosulfapyridine to 84, tacrolimus to 21, mizoribine to 8, gold sodium isothiomalate to 7, actarit to 5, iguratimod to3, and auranofin to 1 patient. Biologics were administered to 33 patients (10.2%); etanercept was administered to 15, abatacept to 6, adalimumab to 4, tocilizumab to 4, infliximab to 3, golimumab to 1, and certolizumab pegol 1 patient. DAS28CRP remission was observed in 149 patients. The disease activity was low, moderate, and high in 53, 74, and 4 patients, respectively. In our study, a few patients showed high disease activity and an increase in the extent of functional disorder. These results may be attributed to the limited number of patients visiting the orthopedic department and the quality of the patients. Conclusions: The study showed the low using ratio of MTX and high using ratio of PSL as much as previous reports. Sixty two percent of RA patients over 80 years of age showed rather low disease activity. Conventional therapy, without the use of bDMARDs, was used to treat 89.8% of the elderly patients with RA. References: Miyamoto S, Sugimura Y, Kashiwagura T, Urayama M, Kobayashi M, et al; Evaluation for treatment of rheumatoid arthritis patients in AORA cohort. The Japanese Society for Clinical Rheumatology and Related Reserch 2015, 27: 135–45. Disclosure of Interest: None declared